The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0167359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Systemic Hypoxia and Hypercapnia on Brain Damage in a Rat Model of Hypoxia-Ischemia

Abstract: Therapeutic hypercapnia has the potential for neuroprotection after global cerebral ischemia. Here we further investigated the effects of different degrees of acute systemic hypoxia in combination with hypercapnia on brain damage in a rat model of hypoxia and ischemia. Adult wistar rats underwent unilateral common carotid artery (CCA) ligation for 60 min followed by ventilation with normoxic or systemic hypoxic gas containing 11%O2,13%O2,15%O2 and 18%O2 (targeted to PaO2 30–39 mmHg, 40–49 mmHg, 50–59 mmHg, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…This could account for why there is currently little consensus regarding whether AQP4 changes in expression levels is upregulated in animal models of stroke, as variations in the stroke model, the duration of reperfusion, and the methods used to determine AQP4 levels can all affect the outcome. For instance, it was observed in a recent study that, while AQP4 protein levels in the cortex are elevated by increasing levels of hypoxia, the effect is exacerbated by additional hypercapnia only in the animals that have undergone the more severe oxygen-deprivation treatments; paradoxically, CO 2 caused a decrease in AQP4 expression in animals given air containing a near-normal amount of oxygen (Yang et al, 2016 ). Oxidative stress probably elicits a similarly graded response, the consequences of which may be therapeutically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…This could account for why there is currently little consensus regarding whether AQP4 changes in expression levels is upregulated in animal models of stroke, as variations in the stroke model, the duration of reperfusion, and the methods used to determine AQP4 levels can all affect the outcome. For instance, it was observed in a recent study that, while AQP4 protein levels in the cortex are elevated by increasing levels of hypoxia, the effect is exacerbated by additional hypercapnia only in the animals that have undergone the more severe oxygen-deprivation treatments; paradoxically, CO 2 caused a decrease in AQP4 expression in animals given air containing a near-normal amount of oxygen (Yang et al, 2016 ). Oxidative stress probably elicits a similarly graded response, the consequences of which may be therapeutically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…no.1063180500) and were mechanically ventilated for 3 h using a small-animal ventilator (SAR-1000, CWE, Ardmore, PA, USA). The tidal volume was set at 9 ml/kg body weight, the respiratory rate was 45 breaths/min, and inspiratory to expiratory ratio was 1:1 [ 22 ]. Mechanical ventilation was performed using a gas tank containing either room air (S group), a gas mixture containing 5% CO 2 , 21% O 2 , 74% N 2 (Hypercapnia group), 16% O 2 , 84% N 2 (Hypoxemia group), or 5% CO 2 , 16% O 2 , and 79% N 2 (HH group).…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20] In our previous study, hypercapnia exerted bene cial effects under mild to moderate hypoxemia and augmented the detrimental effects on the brain during severe hypoxemia in a rat model of hypoxiaischemia. [7] However, BBB dysfunction did not further deteriorate after combined exposure to moderate hypoxia and hypercapnia in this animal model. Moreover, little is known about how the hypercapnia affects molecular and functional changes, such as hypoxia-induced disruption of the TJs, in BBB dysfunction.…”
mentioning
confidence: 61%
“…In our previous study, our ndings suggested that the addition of hypercapnia aggravated the injury after CCA ligation along with severe hypoxemia (PaO 2 < 50 mmHg), but hypercapnia produced protective effects against HIinduced brain damage in rats treated with mild to moderate systemic hypoxia (15% and 18% O 2 , PaO 2 > 50 mmHg). [7] It is possible that the severe injury exceeded the short-term therapeutic potential of exposure to hypercapnia gas. The large volume of ischemic tissue may have overwhelmed any possible bene t of hypercapnia gas exposure.…”
Section: Discussionmentioning
confidence: 99%